Aggression and its Correlates in the Bahamian Community with a Focus on Corporal Punishment - Moxey Adderley , Theresa; Fielding, William J. (International Journal of Bahamian Studies, 2024)
Corporal punishment is commonly used in The Bahamas to correct the behaviour of children. This also risks children becoming aggressive adults. In addition, intimate partner violence is common and takes place in an environment where marital rape is legal. The study investigated associations between corporal punishment, other events in the life of participants and aggression and if aggression is linked to adults using corporal punishment on their own children. An internet-based survey of 5,351 adults (aged 18 or over) living in The Bahamas was used to investigate associations between corporal punishment, other events in the life of participants and aggression. Results: Participants who experienced more childhood events of corporal punishment were more aggressive than others (p < .001, r = .24). Adults who used, or intended to use, corporal punishment on their children, had higher aggression scores and had experienced more childhood corporal punishment events that those adults who did not, or did not intend to, use corporal punishment on their children (p < .001, partial η2 = .01). Negative childhood experiences of violence, lifetime experiences of sexual abuse and workplace bullying were all associated with elevated aggression scores (p < .001). These results suggest that if parents in The Bahamas ceased to inflict corporal punishment on their children society might benefit from lower levels of aggression in the adult population.